Menumbuhkan Kecintaan Pemahaman Agama Sejak Dini Serta Membentuk Karakter Anak Melalui Pembinaan Al-Qur’an di Lingkungan TPA Untuk Anak-Anak Meningkatkan kualitas Pendidikan Agama di Era Digital - indah mukaromah (Fakultas Ushuluddin dan Komunikasi Islam, 2025)
Instilling a love for religious understanding from an early age plays a vital role in shaping the character of morally upright children. The Qur'anic Education Center (TPA) serves as a strategic environment for embedding Islamic values, especially through structured and continuous Qur'anic guidance. In today’s digital era, religious education faces increasingly complex challenges due to the influence of technology on children's behavior and attention. Therefore, integrating learning methods that align with technological developments is essential to enhance the effectiveness of religious instruction. This study aims to analyze the role of TPA in fostering a love for the Qur’an, shaping children's character, and improving the quality of religious education amidst digital transformation. Using a qualitative approach through observations and interviews in several TPAs, it was found that consistent Qur'anic guidance effectively instills religious values, discipline, and strengthens children's moral foundations from an early age. These findings indicate that Qur’an-based guidance in TPAs significantly contributes to improving the quality of religious education that is adaptive to digital challenges.